Image processing improvements afford second-generation handheld optoacoustic imaging of breast cancer patients - Kukacka, Jan; Metz, Stephan; Dehner, Christoph; Muckenhuber, Alexander; Paul-Yuan, Korbinian; Karlas, Angelos; Fallenberg, Eva Maria; Rummeny, Ernst; Juestel, Dominik; Ntziachristos, Vasilis (Photoacoustics, 2022)
Background: Since the initial breast transillumination almost a century ago, breast cancer imaging using light has been considered in different implementations aiming to improve diagnostics, minimize the number of available biopsies, or monitor treatment. However, due to strong photon scattering, conventional optical imaging yields low resolution images, challenging quantification and interpretation. Optoacoustic imaging addresses the scattering limitation and yields high-resolution visualization of optical contrast, offering great potential value for breast cancer imaging. Nevertheless, the image quality of experimental systems remains limited due to a number of factors, including signal attenuation with depth and partial view angle and motion effects, particularly in multi-wavelength measurements. Methods: We developed data analytics methods to improve the accuracy of handheld optoacoustic breast cancer imaging, yielding second-generation optoacoustic imaging performance operating in tandem with ultrasonography. Results: We produced the most advanced images yet with handheld optoacoustic examinations of the human breast and breast cancer, in terms of resolution and contrast. Using these advances, we examined optoacoustic markers of malignancy, including vasculature abnormalities, hypoxia, and inflammation, on images obtained from breast cancer patients. Conclusions: We achieved a new level of quality for optoacoustic images from a handheld examination of the human breast, advancing the diagnostic and theranostic potential of the hybrid optoacoustic-ultrasound (OPUS) examination over routine ultrasonography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast cancer; Image quality enhancement; In vivo imaging; Multispectral optoacoustic tomography; Tumor-associated microvasculature; Ultrasound